2017
DOI: 10.1007/s41230-017-6094-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cu addition on microstructure and mechanical properties of as-cast Mg-6Zn magnesium alloy

Abstract: F or decades, magnesium alloys have wide applications in the aerospace, transportation and mobile electronics industries due to their advantages such as extremely low density and good damping capacity, high specific strength and stiffness, excellent machinability and good castability [1][2][3][4] . However, commercial magnesium alloys provide limited mechanical properties, which hinder their widespread applications [5] . More particularly, to the best of our knowledge, the Mg-Zn binary alloys possess coarse de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Among commercially available magnesium alloys, Mg–Zn-based alloys are of particular interest because of their good age-hardening effects. However, they have coarse dendritic microstructures, tend to exhibit extensive hot cracking, and have critical shrinkage cavities and porosities; these characteristics deteriorate the mechanical properties [13]. Previous studies have shown that Cu significantly enhances the aging strength and improves the mechanical properties of magnesium alloys [1316].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among commercially available magnesium alloys, Mg–Zn-based alloys are of particular interest because of their good age-hardening effects. However, they have coarse dendritic microstructures, tend to exhibit extensive hot cracking, and have critical shrinkage cavities and porosities; these characteristics deteriorate the mechanical properties [13]. Previous studies have shown that Cu significantly enhances the aging strength and improves the mechanical properties of magnesium alloys [1316].…”
Section: Introductionmentioning
confidence: 99%
“…However, they have coarse dendritic microstructures, tend to exhibit extensive hot cracking, and have critical shrinkage cavities and porosities; these characteristics deteriorate the mechanical properties [13]. Previous studies have shown that Cu significantly enhances the aging strength and improves the mechanical properties of magnesium alloys [1316]. According to reports by Zhu et al and Wang et al Mg–6Zn– x Cu–0.6Zr alloys have better yield strength, ultimate tensile strength, and elongation, when the added Cu is 0.5–1.0 wt-% [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The Al 4 Ce phase has some advantages such as high melting point, high stability and insolubility in α-Mg matrix. At the same time, the formation of Al 4 Ce reduces the β-Mg 17 Al 12 content, and then the Al content in the matrix decreases [21]. Al element has a certain initiative in the whole process of forming the Al 4 Ce layer.…”
Section: Deformation Mechanism Of Mg-ce Intermediate Alloy Chipsmentioning
confidence: 98%
“…However, Wang et al [12] demonstrated that ZK60 alloy has a rough dendritic microstructure that makes it prone to hot cracking, which degrades the mechanical properties. Moreover, Zhang et al [13] reported that the copper (Cu) element aided in significant increase in the age–strength and improvement in the mechanical properties of magnesium alloys. Zhu et al and Chen et al reported that the Mg–Zn–Cu alloys exhibited the best age-hardening phenomenon and tensile properties at room temperature when Cu was added in the range of 0.5–1.0 wt-% during the isothermal ageing process at 180°C [14,15].…”
Section: Introductionmentioning
confidence: 99%